Base deformation’s features during deep foundation pit excavation - Zotsenko, Mykola; Vynnykov, Yuriy (Academic journal Industrial Machine Building Civil Engineering, 2020)
The problems of estimating the stress-strain state of the foundations during the deep foundation pits installation are considered. The results of finite element calculations in the plane formulation of the stability of the pit walls and the retaining structures' operation under dense urban development are presented. It is proved that the proposed method specifies the calculation of determining the impact of the new building on existing buildings and structures, which enables assigning the design of retaining structures from drilled piles on the conditions of normal further operation of existing facilities. It is established that the parameters of the structures retaining the walls of deep foundation pits in the presence of existing buildings, should be assigned based on the actual condition of these buildings and the allowable additional deformations.